As características do sistema de controle de gestão em organizações do terceiro setor: estudo de caso em fundações empresariais - Silva, Rinaldo Assis da (2018)
The objective of this work was to identify which level the practices and mechanisms adopted for the management control of corporate foundations studied are able to lead them to the achievement of their objectives. For the study, was used to study the type qualitative, descriptive nature, addressed through a case study, with data obtained through research the internal documents and interviews and treated through documentary analysis and content. The theoretical approached the topics managerial control; organizational theories; types of managerial control; tools of managerial control; third sector; management of third sector; legal nature and characteristics of the third sector entities; and regulatory framework of the third sector. Based on the interviews, it was possible to identify from the point of view of the objectives, that each foundation develops its structure of control as your company controlling the routes, the findings of this study show that the foundations have similarities and differences in the ways of management, it should be noted that the similarities are more frequent within the structure, processes and control types. The structure all feature information system, and the type of control by a result, with the exception of the Avon Foundation. The processes there are also some similarities, all use planning and evaluation of results, but the foundations Holcim, DPaschoal and Foundation X do not use corrective decisions. The differences occurin greater proportion in regard control tools, all using the financial tools budget and budget planning, with the exception of the Avon Foundation that does not use the budget planning tool Among the non-financial tools highlights the Bechmarking and Intellectual Capital that are used by all the foundations, Corporate Governance is not only used by DPaschoal. The Balanced Scorecard to be used by foundations and crooked, Holcim, Cyrela and Foundation "X" is basically intended to measure performance on social return. In common among foundations, there is not any type of reward in function of the ranges. It is also emphasized in studies that the strategic planning of the foundations are defined in function of the social actions, with the prospect of long-term and acting as advisor of the targets. We found also in relation to the accounting aspects that the foundations surveyed have not informed about their daily routines, it was observed that there was on the part of the respondents any interest and commitment to highlight or show how the application of accounting for the management of foundations. The foundations crooked, Holcim, Cyrela, DPaschoal and "X" develop the practice of internal form, by their sponsors, companies and foundations Arcellor mital and Avon use services from third party companies. The results found evidences how the corporate foundations still feature of limitation on greater transparency about its characteristics of management, these difficulties presented fall above all on achieving interview a manager responsible for information that are fundamental to the studies, in addition to the limitation of time that they offe.